A nosocomial cluster of Roseomonas mucosa bacteremia possibly linked to contaminated hospital environment. Issue 8 (August 2020) - Okamoto, Koh; Ayibieke, Alafate; Saito, Ryoichi; Ogura, Kenichi; Magara, Yuki; Ueda, Reiko; Ogawa, Hina; Hatakeyama, Shuji
Abstract: Roseomonas, a genus of pink-pigmented glucose non-fermentative bacteria, has been associated with various primary and hospital-acquired human infections; however, to our knowledge, its nosocomial transmission has never been reported. Clinical and epidemiological investigations were carried out after two cases of R. mucosa bacteremia occurred in our hospital in 2018. Environmental samples were taken of environmental surfaces prone to water contamination in the wards and cultured. The two clinical isolates and all environmental isolates that showed growth of pink colonies were identified using matrix-assisted laser desorption/ionization time of flight mass spectrometry and 16S rRNA gene sequencing. Pulse-field gel electrophoresis (PFGE) was performed and fingerprinting software was used to analyze the DNA restriction patterns and determine their similarity. Two patients who developed R. mucosa bacteremia had received care from the same treatment team. Of 126 environmental samples, five showed growth of R. mucosa . Using 80% similarity as the cut-off, PFGE analysis revealed that the isolates from the two patients' blood cultures and three environmental isolates belonged to the same clone. The hospital water environment was contaminated with the same clone of R. mucosa that caused bacteremia in the two patients, suggesting nosocomial transmission linked to contaminated environment. Increased vigilance is needed to monitor the emergence of Roseomonas in healthcare settings.